Pengaruh Gaya Kepemimpinan Tranformasional, Perceived Organizational Support dan Person-Job Fit Terhadap Kinerja Pegawai ASN BKAD Kabupaten Kulon Progo - Agus Kurniawan; Ema Nurmaya; Abdul Choliq Hidayat (CV. Ulil Albab Corp, 2025)
This study aims to analyze the effect of Transformational Leadership Style, Perceived Organizational Support and Person-Job Fit on the Performance of ASN Employees at BKAD Kulon Progo Regency. Using an associative approach, primary data were collected through an online questionnaire distributed to 70 respondents who ASN employees using the purposive sampling method. Data analysis was carried out using multiple linear regression. The result showed that Transformational Leadership Style, organizational support, and fit between individuals and jobs contributed significantly to improving employee Performance at BKAD Kulon Progo Regency. This finding emphasizes the importance of implementing a transformational leadership style, perceived organizational support and person-job on employee performance